AUTOMATIC POWER FACTOR CONTROL (APFR) CAPACITOR SHUNT UNTUK OPTIMALISASI DAYA REAKTIF MENGGUNAKAN METODE INVOICE (CASE STUDY PDAM) - Safrizal Safrizal (Jurnal DISPROTEK, 2015)
Power consumption in the industry generally is inductive which causes behind the current wave of the voltage waveform. One indicator of the quality of electric power (power quality) is good is when Power Factor> 0.85. Lag. Most of the electrical load on the Regional Water Company (PDAM) is inductive, it leads to lower power factor value 0,85. Lag. Sebagian besar beban listrik pada Perusahaan Air Minum Daerah (PDAM) adalah bersifat induktif, hal ini menyebabkan rendahnya nilai faktor daya